Critical Techniques in Learning English: a Comprehensive Review (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Learning English as a second language is a complex process that requires a range of critical techniques to facilitate effective language acquisition. This article provides a comprehensive review of various critical techniques in learning English, including immersion, active engagement, vocabulary acquisition, reading and writing strategies, and cultural competence. By understanding and implementing these techniques, learners can enhance their language proficiency and communicative skills. The article highlights the importance of integrating these techniques into language learning programs and offers recommendations for educators and learners alike.